Teachers’ and Students’ Perceptions on Computer-Based Test toward the Curriculum Used in SMKN 11 Bandung - Rizka Maulina Wulandari; Dian Palupi; Jannatul Laily Noviabahari (Lembaga Pengembangan Kinerja Dosen, 2022)
Computer-based test (CBT) is one of evaluation ways to develop the current curriculum because it deals with the demand of ICT development which students have to be able to gain their knowledge by using the advanced of technology. Besides, the current curriculum is intended to provide learners with a broad range of learning experiences in order to help them develop better attitudes, abilities, and knowledge. It is also the most important factor that helps learners become more capable and effective as citizens of the world. Thus, this study aims at investigating teachers’ and students’ perceptions on applying CBT toward the implementation of curriculum used in SMKN 11 Bandung. Descriptive qualitative design was employed using a 20-item Likert-scale questionnaire and an interview guideline as the research instruments. The findings showed that teachers and students agreed that the assessment for the final test applying CBT in their school already implemented the current curriculum and it could be used to evaluate the learning condition in the school. Meanwhile, in conclusion, teachers mostly agreed that the questions written on CBT were already appropriate with their teaching during the learning process.